2022
DOI: 10.21203/rs.3.rs-2281620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Down regulation of Cathepsin W is associated with poor prognosis in Pancreatic cancer

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is associated with a very poor prognosis. Therefore, there has been a focus on the identification of new biomarkers for the early diagnosis of PDAC and prediction of patient survival. Genome-wide RNA and microRNA sequencing were used using bioinformatics and Machine Learning approaches to identify differentially expressed genes (DEGs) followed by validation in additional cohort of PDAC patients. Methods: genome RNA sequencing and clinical data from pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…This suggests that these proteins may be potential targets for immunotherapy in EC patients [ 40 ]. The predictive and diagnostic use of CTSW in pancreatic ductal adenocarcinoma (PDAC) was suggested by data presented by Khojasteh-Leylakoohi et al The results of the survival study showed that PDAC patients had a reduced survival rate due to overexpression of hsa.miR.153.1, hsa.miR.539 and hsa.miR.412 and decreased expression of hsa.miR.642a, hsa.miR.363, CD22, BTNL9 and CTSW [ 41 ]. Studies in dogs, particularly those with epitheliotropic lymphoma (a type of cutaneous T-cell lymphoma), have identified microarray probes for CTSW, TRAT1 and KLRK1 as potential tools to differentiate this lymphoma from other forms of interface dermatitis.…”
Section: Involvement Of Ctsf and Ctsw In Malignanciesmentioning
confidence: 99%
“…This suggests that these proteins may be potential targets for immunotherapy in EC patients [ 40 ]. The predictive and diagnostic use of CTSW in pancreatic ductal adenocarcinoma (PDAC) was suggested by data presented by Khojasteh-Leylakoohi et al The results of the survival study showed that PDAC patients had a reduced survival rate due to overexpression of hsa.miR.153.1, hsa.miR.539 and hsa.miR.412 and decreased expression of hsa.miR.642a, hsa.miR.363, CD22, BTNL9 and CTSW [ 41 ]. Studies in dogs, particularly those with epitheliotropic lymphoma (a type of cutaneous T-cell lymphoma), have identified microarray probes for CTSW, TRAT1 and KLRK1 as potential tools to differentiate this lymphoma from other forms of interface dermatitis.…”
Section: Involvement Of Ctsf and Ctsw In Malignanciesmentioning
confidence: 99%
“…[24] Cathepsin W has been recently studied for its role in immunity [25], virus infection [26] and tumour prognosis. [27] Cathepsin X/Z is highly expressed in monocytes, T-lymphocytes, macrophages, and dendritic cells and it is thought to have roles in phagocytosis, maturation, proliferation, migration, adhesion, and signal transduction in immune cells. It is also expressed in cells of the gastrointestinal tract, non-hematopoietic bone marrow cells and brain cells.…”
Section: Cysteine Cathepsinsmentioning
confidence: 99%